PENGARUH TINGKAT SUKU BUNGA, KUALITAS PELAYANAN DAN PENDAPATAN USAHA TERHADAP KEPUTUSAN PENGAMBILAN KREDIT (STUDI KASUS PADA NASABAH BNI KCU UNDIP SEMARANG) - Yulita Martha Chrisanti; Saryadi Saryadi (Universitas Diponegoro, 2017)
This research was motivated by fact that there’s a high demand of find distribution for capital that is safe, fast, and easy. BNI KCU UNDIP must pay attention to the interest rate that given, effect of service quality, and the customer’s business income for making customers interest to use their service.This study aims to determine the influence of interest rate, service quality, and business income towards credit decision-making at BNI KCU UNDIP. The sample in this reseach is 100 respondens who are debitors BNI KCU UNDIP. This study used purposive samplng as a sampling techniques of data collection using questionnaires. The analytical method used was simple and multiple regression analysis, the validity and reliability.Based on the result analysis, variable the interest rate, quality of service, and business income have a positive influence of the credit making decision. Variable the quality of service have the most influence is as much as 0,355. Variable business income have influence of 0,279 and variable interest rates have influence of 0,123. Simultaneously a variable the interest rates, quality of service, and business income having contributions amounting to 36,3% of the credit decision-making.The advice that can be provided, BNI KCU UNDIP should be able to maintain and improve the quality of service well, physically and human resources, maintain interest rates to be able to compete with similar bank and business income in accordance with the credit.